Três momentos da história da acentuação portuguesa - Massini-Cagliari, Gladis [UNESP] (2014)
This article examines the lexical stress positioning in three moments of Portuguese diachrony: in its Latin origin, in medieval times (the so called Archaic Portuguese, of GalicianPortuguese), and in contemporary times, comparing Brazilian and European Portuguese. Two analysis are presented: the first one, based on non-linear Phonology theories, and the second one, based on Optimality Theory. The article shows that the rhythmic chance that affected Portuguese in its diachronic trajectory from Latin to contemporary days is not based in lexical stress positioning, which is still very close to what happened in the original Latin phase of the language.